Penerapan Metode Menebalkan Garis Putus-Putus dalam Meningkatkan Koordinasi Mata dan Tangan Anak Usia 4-5 Tahun Di TK Aisyiyah Bustanul Athfal II Perumnas - Tahir, Yusuf; Haidar, Dian; Patiung, Dahlia; Mattemmu, Evarastina; Praningrum, Widya (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2022)
Giving stimulation in early childhood is very important for optimizing children's development, including fine motor skills. It is important to optimize fine motor development stimulation because it will affect the child's readiness to maximize the movements of the wrist and fingers. This also affects the coordination of the child's eye and hand functions so that he can process the information he receives at the same time. This study aims to determine the improvement of the child's eye and hand coordination after applying the method of thickening the dotted line to children aged 4 to 5 years in community service research through service learning at TK Aisyiyah Bustanul Atfhal II Perumnas Makassar City with a total of 4 participants. children. In its application, it uses a dotted line patterned drawing paper instrument, an observation sheet, and an evaluation sheet for the implementation of the intervention. The data obtained were analyzed using descriptive statistics. The results of this research show that the application of thickening the dotted line is effective in improving children's hand and eye coordination in carrying out activities simultaneously. This study implies that the development of hand-eye coordination in stimulated children has different speeds.